Introduction to the Mathematical Theory of Control Processes: Linear Equations and Quadratic Criteria - Bellman, Richard (New York : Academic Press, 1967)
This first volume covers the fundamentals of the calculus of variations, dynamic programming, discrete control processes, use of the digital computer, and functional analysis.
Includes bibliographical references and index.
ne 26/03/2018
Loan
Keywords: Control Theory